Environmental considerations in M&A mining transactions - Rodríguez Mariátegui Canny, Luis (2023)
The purpose of this article is to point out the relevant environmental risks in mining transactions, from the point of view of the authors’ experience. The different stages of the mining industry are described, and then the common environmental impacts associated with each of them, as well as the sources of legal, contractual, environmental management instruments and permits, selfimposed and other obligations and commitments that result in liabilities.In the framework of mining transactions, the following are detailed the investigations to be carried out by the parties to the contracts, the identification of the risks identification of risks, the assignment of responsibilities and the treatment to be given to the resolution of the and the treatment to be given to the solution of contingencies and impacts. Finally, it develops the applicable legislation from the perspective of international law.